Need Analysis of English Material for Vocational School of Health: A Case Study at One School at Karanganyar - Phoumchay Vongvilay; Dwi Kartika; Malikatul Laila (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
This research aims to identify the students’ prospective professional need in learning English writing skills, to identify the style of learning that students preferred in learning English writing skills, and to reveal the incompetent that students need to improve in writing. This study required stratification that minimizes sampling errors to zero level. In this study, the 140 students from the second grade were chosen to be the participant. The questionnaire was used to be instruments to get the responses from the students about the learning needs. This study found that students need writing sentences correctly in learning English writing. The style of learning that students needed to learn English writing skills was in a small group more than group work. The topic that students preferred in learning is the topic about health as their background school is health, nursing, and pharmacy program. Students actually needed to learn English by themselves. The idea expansion was incompetent that students need to improve in writing. It is hoped that all these needs analyzed can be taken into attentiveness in increasing an ESP course for students.